Community engagement in global health education supports equity and advances local priorities: an eight year Ecuador-Canada partnership - Misra, Shivali; Doucet, Alison; Morales, Juana; Andersson, Neil; Macaulay, Ann; Evans, Andrea (Revue canadienne de l’éducation médicale, 2018)
Background: Global health education initiatives inconsistently balance trainee growth and benefits to host communities. This report describes a global health elective for medical trainees that focuses on community engagement and participatory research to provide mutually beneficial outcomes for the communities and trainees. Methods: An eight-year university–community partnership, the Chilcapamba to Montreal Global Health Elective is a two-month shared decision-making research and clinical observership experience in rural Ecuador for medical trainees at McGill University, Canada. Research topics are set by matching community-identified priorities with skillsets and interests of trainees, taking into consideration local potential impact. Results: Community outcomes included development of a Community Health Worker program, new collaborations with local organizations, community identification of health priorities, and generation of health improvement recommendations. Collaborative academic outputs included multiple bursary awards, conference presentations and published manuscripts. Conclusion: This medical global health elective engages communities using participatory research to prioritise socially responsible and locally beneficial outcomes.